Correlation between uric acid levels and bone mineral density in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Zhao, Hang; Qi, Cuijuan; Zhang, Yunjia; Ren, Luping; Chen, Shuchun (Frontiers in Endocrinology, 2025)
PurposeTo explore the controversial relationship between uric acid (UA) levels and bone mineral density (BMD) in patients with type 2 diabetes mellitus (T2DM).Patients and methodsThe PubMed, Embase, and Cochrane Library databases were searched using keywords and related words. Study quality was evaluated using the Newcastle-Ottawa Scale. Studies retrieved in the literature search were systematically screened to extract information and data based on predefined inclusion and exclusion criteria. RevMan version 5.3 and Stata Release 13.0 were used for statistical analysis. Results are expressed as mean difference (MD) and corresponding 95% confidence interval (CI). Heterogeneity was evaluated using the I2 and Q tests.ResultsThis meta-analysis included 10 studies comprising 5,717 patients with T2DM. Study quality ranged from moderate to high. Results of comparative analyses were as follows: normal BMD versus (vs.) osteoporosis (OP) in females, MD −13.83 μmol/L (95% CI −41.69 to 14.03); I2 = 7%; P=0.30); normal BMD vs. osteopenia in females, MD −12.41 μmol/L (95% CI −37.81 to 12.99; I2 = 0%; P=0.92); normal BMD vs. abnormal BMD (osteopenia/OP), MD −23.82 μmol/L (95% CI −33.50 to −14.13; I2 = 0%; P=0.44); and osteopenia vs. OP, MD −22.35 μmol/L (95% CI −29.55 to −15.15; I2 = 5%; P=0.39). No publication bias was observed.ConclusionCompared with normal BMD, abnormal BMD (osteopenia/OP) was associated with lower UA levels. Compared with osteopenia, OP also showed lower UA.Systematic review registration: